Navigating Implementation Challenges of Stunting Solutions in Indonesia's Health Programs - Wasono, Wasono; Sukmana, Hendra (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Indonesia faces a significant public health issue with fifth-highest stunting prevalence among toddlers, especially in East Java, and local efforts are being implemented to reduce rates. Specific Background: Klurak village government's stunting prevention programs, involving Posyandu cadres and midwives, face challenges due to communication, resources, disposition, and bureaucratic structure, as per Edward III's implementation theory. Knowledge Gap: While stunting programs are in place, the extent to which these programs effectively address local needs and barriers, particularly through an administrative lens, remains underexplored. Aims: This study aims to analyze the implementation of stunting prevention programs in Klurak Village using Edward III’s four-indicator framework and identify the key sectors hindering or supporting effective implementation. Results: Findings suggest that the stunting prevention program is moderately effective. Communication among village stakeholders is integrated but limited by budget constraints, while resources, particularly in human capacity and infrastructure, are inadequate. Despite positive dispositions among health workers, bureaucratic inefficiencies hinder maximum implementation. Novelty: The study provides a rare, localized analysis of stunting prevention through a public administration framework, offering practical insights into grassroots-level health governance in Indonesia. Implications: The research highlights the need for better resource allocation, continuous socialization efforts, and enhanced inter-agency collaboration to improve stunting prevention outcomes in rural settings. Highlights: Communication Gaps: Enhance stakeholder interaction to improve stunting awareness. Resource Needs: Adequate resources are essential for program effectiveness. Bureaucratic Issues: Structural inefficiencies hinder health program implementation. Keywords: Stunting, Klurak Village, Public Health, Program Implementation, Edward III Theory